Dithieno[3, 2-b:2′, 3′-d]arsole-containing conjugated polymers in organic photovoltaic devices. Issue 20 (24th April 2019) - Green, Joshua P.; Cha, Hyojung; Shahid, Munazza; Creamer, Adam; Durrant, James R.; Heeney, Martin
Abstract : Dithieno[3, 2- b :2′, 3′- d ]arsole containing donor polymers are reported and investigated in organic solar cell devices for the first time. Abstract : Arsole-derived conjugated polymers are a relatively new class of materials in the field of organic electronics. Herein, we report the synthesis of two new donor polymers containing fused dithieno[3, 2- b :2′, 3′- d ]arsole units and report their application in bulk heterojunction solar cells for the first time. Devices based upon blends with PC71 BM display high open circuit voltages around 0.9 V and demonstrate power conversion efficiencies around 4%.